Dynamic Prioritization of Path for Quality-of-Service Differentiation in Multi-Priority Traffic - Fatemeh Banaie; Seyed Amin Hosseini-Seno; Mohammad Hossein Yaghmaee; Rahmat Budiarto (IAES Indonesia Section, 2014)
The emergence of value added services relying on a higher interactivity has altered the requirements of current transport network. Diverse traffic classes are processed by a large-scale optical network, imposing a more efficient utilization of their network infrastructure resources. Such services generally cross multiple domains, but inter-domain path computation algorithms still have some limitations. This paper describes a priority based path computation algorithm to meet all QoS requirements with the available capacity. The proposed algorithm increases the rate of successful replies while minimizing the blockage in network. The dynamic traffic is classified into high and low priority, so it improves emergency response in network.